KONSEKUENSI DARI WORKLOAD, DAN KECERDASAN EMOSIONAL PARA PEGAWAI DI LINGKUNGAN PEMERINTAH DI P2KBP3A KABUPATEN BANDUNG - Rita Mustikawati; Sindrawati Sindrawati; Muhammad Syukrullah Abdullah (Universitas Bina Taruna Gorontalo, 2023)
G This study aims to determine the effect of workload and emotional intelligence of employees on employee burnout. The method used in this study uses a quantitative approach using multiple linear regression analysis with the help of SPSS 25 for windows software. The sample in this study were 120 employees at P2KBP3A Bandung district. The results of the study show that workload has a positive and significant relationship with burnout, which indicates that the higher the workload faced, the more likely employees are to experience burnout. Emotional intelligence reduces the impact of workload on burnout. Efforts to reduce workload by increasing emotional intelligence help prevent burnout. Increasing employee emotional intelligence can be an effective strategy in reducing burnout. This research provides insight into the factors that can affect employee burnout in the government environment. The practical implications of these findings can assist human resource management in developing effective strategies and programs to prevent burnout and improve the welfare of employees within the Government, especially P2KBP3A Bandung Regency UPTD P5A Rancaekek.